Design of Compact Multiband Microstrip BPF Based on Fractal Open-Ring Configuration - Hayder Ahmed; Hussain Hammas; Mohammed Hussan (Engineering and Technology Journal, 2018)
Multiband bandpass filters (BPFs) are one of the core elements in the multi-services wireless communication systems. For this purpose, this paper presents a design of a compact multiband microstrip BPF design based on fractal open loop configuration. The proposed filter structure is composed of an array of equal side length open-loop resonators; each with different fractal iteration level. More specifically, the modified Minkowski fractal geometry has been adopted to be applied to the conventional open-loop rectangular resonator. The resulting filter configuration has an array of different open-loop structures corresponding to various iteration levels. The simulation of the presented filter is performed using the EM Sonnet software package environment. The proposed filter is printed on a substrate of dielectric constant is 10.8 with thickness 1.27 mm. A filter structure with three resonators having different fractal iteration levels offers a triple band frequency response around 3.05 GHz, 2.05 GHz, and 1.68 GHz. Each of the three resonant bands is attributed by a distinct resonator according to the iteration levels. Additional resonant bands can be realized using extra loops with higher iteration levels.